Zagrożenie dla „amerykańskiego snu”. Ekonomiczne i etyczne refleksje nad kryzysem finansowym lat 2007−2008 i późniejszą recesją - VER EECKE, Wilfried; DĄBKOWSKI, Grzegorz (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
I start by summarizing the views of Keynes on recessions and of Schumpeter on economic growth. I then point out that recently some economists have taken a socio−political perspective in looking for causes for the financial crisis and the handling of the recession which followed the financial crisis. Such a socio−political per− spective introduces an ethical dimension in economic thinking. I then connect that ethical dimension of economic thinking to Musgrave’s ethical economic concept of merit goods and my own creation of merit good categories. Next, I contrast the Reinhart/Rogoff view of the financial crisis with the one developed by Reich/Rajan. In my conclusion I then show how the Reich/Rajan approach makes use of seven of my eleven merit good categories to clarify the 2007−2008 financial crisis and the subsequent recession. In doing so I am able to highlight the ethical dimension in the Reich/Rajan analysis of the recent financial crisis and the recession it caused.